Nurse's attitude and acceptance of coronavirus disease 2019 vaccination in maitma district Hospital, Abuja, Nigeria - Olaolorunpo Olorunfemi; Francisca Ogochukwu Uwabunkeonye; Joseph Adekunle Adebiyi; Adewole Peter Akindipe; Oluwaseun Oluwafunmilayo Abiodun (Wolters Kluwer Medknow Publications, 2023)
Background: The development of coronavirus disease 2019 (COVID-19) vaccines is a major challenge; and after clinical development, another critical problem is the acceptance of the vaccine among health workers, particularly nurses, who are expected to persuade other members of the community to be vaccinated against the virus. As a result, if success is to be recorded, it is necessary to examine nurse's attitudes and acceptability level for proper policy in Nigeria's health sector. Aim: The aim of study was to determine the attitude and acceptance of COVID-19 vaccination among nurses. Methodology: A cross-sectional design was used, and data were collected using a validated self-structured questionnaire. The IBM SPSS Statistics 23 software was used to analyze the data, and the results were presented using frequency tables, percentages, means, standard deviations, and Chi-square analysis. Results: According to the findings of this study, most of the respondents feel that COVID-19 vaccination is good for them (3.2 ± 4.0), but this does not translate to acceptance due to concerns about side effects, which results in a lack of trust in the vaccine' safety, with a mean of 3.4 ± 4.3. Furthermore, the findings revealed a mean acceptance score of 2.96 ± 2.6, indicating that just above average number of the participants welcomed COVID-19 vaccination. Conclusion: This study concluded that the respondents had a positive attitude toward COVID-19 vaccination and acceptance is relatively low and this was as a result of their concerns over vaccine safety and side effects. Sociodemographic variables such as religion, level of education, and ethnic group were also implicated. Therefore, to increase nurses' acceptability, we advocate a constant and devoted effort to improve political commitment, increase awareness, and disseminate information regarding the safety, side effects, and effectiveness of the COVID-19 vaccination.